DINAMIKA IDEOLOGISASI GENDER DALAM KEPUTUSAN-KEPUTUSAN RESMI MUHAMMADIYAH - Dzuhayatin, Siti Ruhaini (Sunan Kalijaga State Islamic University & The Asia Foundation, 2012)
Gender is one of the core dimensions upholds the collective identity which is noticeably pertinence to the context of Muhammadiyah known as the modern Islamic organization in Indonesia. As the continuum of the above selection of dimensions, gender ideology of Javanese priyayi which reflects senior junior partnership is made available as the stock of knowledge for its identity, not only governs the micro-context of family relation but more obviously operates as the backbone structure of the organization. The endurance of such a structure is laid by the background of its founders who were mainly the elites of the Javanese santri-priyayi in its inception era and politically sustained by the macro-structure of the Indonesian state which has been primarily dominatedÂ by the Javanese priyayi . This reciprocal influence is made possible for such a gender regime to operate within this organization over a hundred year existence with the legitimacy of religious teachings which is arbitrarily a selective mechanism of normative ground.